2016
DOI: 10.1371/journal.pone.0164414
|View full text |Cite
|
Sign up to set email alerts
|

Outlining the Ancestry Landscape of Colombian Admixed Populations

Abstract: The ancestry of the Colombian population comprises a large number of well differentiated Native communities belonging to diverse linguistic groups. In the late fifteenth century, a process of admixture was initiated with the arrival of the Europeans, and several years later, Africans also became part of the Colombian population. Therefore, the genepool of the current Colombian population results from the admixture of Native Americans, Europeans and Africans. This admixture occurred differently in each region o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
85
2
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 35 publications
9
85
2
3
Order By: Relevance
“…Using data from the 46 AIM-Indels, pairwise F ST genetic distances were calculated between the five Patagonian populations from this study, and samples from six Argentinian provinces [15], six South American populations from Brazil [23], Bolivia [24] and Colombia [25,26], as well as the European, African and Native American HGDP-CEPH reference populations [22] (S5 Table).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Using data from the 46 AIM-Indels, pairwise F ST genetic distances were calculated between the five Patagonian populations from this study, and samples from six Argentinian provinces [15], six South American populations from Brazil [23], Bolivia [24] and Colombia [25,26], as well as the European, African and Native American HGDP-CEPH reference populations [22] (S5 Table).…”
Section: Resultsmentioning
confidence: 99%
“…Dye-labeled amplified fragments were separated and detected using an ABI3130 Genetic Analyzer (Life Technologies), and automated allele calls were obtained with GeneMapper v.3.2 (Life Technologies). This panel showed to be highly informative to analyze genetic admixture in different Latin-American populations, including Argentina [15], Brazil [23], Bolivia [24] and Colombia [25,26].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Study population. Strains analyzed in this study were isolated from patients recruited in the context of a multi-centric study based in Latin America 50,51 . Sequences used in the present work are largely overlapping with those reported in a phylogenetic analysis on Latin American HP strains 29 .…”
Section: Methodsmentioning
confidence: 99%
“…Geographically, the Coffee Belt region is in the Cordillera Central of the Colombian Andes. The ancestry analysis of this region has identified a high European and Native American genetic contribution and a low value of African ancestry [36]. The population of our study self-reportedly identified as mestizo and white individuals and a minority of Afro-descendant ethnic origin.…”
Section: Resultsmentioning
confidence: 90%